UPAYA MENINGKATKAN PEMAHAMAN HURUF VOKAL MELALUI MEDIA PUZZLE BAGI ANAK TUNAGRAHITA SEDANG KELAS 1/C1 DI SLB KARTINI BATAM - Siti - Aminah (Jurnal Penelitian Pendidikan Khusus, 2013)
Efforts to enhance understanding through media vowels Tunagrahita Puzzles for children in special-ed medium classes in SLB Kartini Batam. This study originated from a concern for children Tunagrahita were to be trained how to read. The study is motivated from the fact that occur in school children are not able to read. This research aims to improve understanding of the child Tunagrahita vowels were. This study used a qualitative approach in research methodology class action (PTK). Approach to action research conducted within two (2) cycles. Cycle I read through the media shows the implementation of the puzzle has been no improvement. However, motivation and self-confidence is not in accordance with what is expected. On the implementation of the second cycle students need to be supervised and demonstrated ways a good read. Researchers have not been able to guide students in implementing reading. From the results of this study can be completed given that the action in the second cycle was obtained increased draft letter Tunagrahita child is in the letter of understanding training activities should be routine, so hopefully Tunagrahita children were able to understand the concept of a shared or private letters.